Water and Nutrient Management Guidelines for Greenhouse Hydroponic Vegetable Production in Florida - Robert C. Hochmuth; Natalie B. Parkell; Wanda L. Laughlin; Sean C. Rider (EDIS)
Many small farms are implementing greenhouse hydroponic systems. Perhaps the most challenging aspect of crop management for smaller growers is the control of water and nutrient delivery in a soilless media system. This 7-page fact sheet focuses on relatively inexpensive strategies to help small growers know both when to start irrigation events and how long to run a single event when growing in soilless media. Written by Robert C. Hochmuth, Natalie B. Parkell, Wanda L. Laughlin, and Sean C. Rider, and published by the Horticultural Sciences Department, December 2015.